THE STRENGTHENING HALAL TOURISM BASED ON PROPHETIC ISLAMIC PARADIGM THROUGH THE HISTORICAL SOCIAL INFERENCE OF THE SASAK, SAMAWA, AND MBOJO-NTB - Nurjannah S; Rina Rohayu. H; Khudzaifah Dimyati; Absori Absori (istinbath, 2019)
This article discusses the strengthening of halal tourism based onthe Islamic Prophetic Paradigm. Halal tourism built in West Nusa Tenggara is unclear and final about the direction and concept. Many parties are hesitant and criticized about the title of the halal destination carried by the regional government. Is it true that the government is committed to creating a religious and halal tourism environment? Is it in line with the historical social inference of the NTB community in wrapping the cultural customs of the tribes in the region?. This study uses the sociological method of jurisprudence, with the approach of the Islamic prophetic paradigm.Furthermore, it uses the procedureof historical social inference to find convergence between Islamic values and the past, social aspects of the three major tribes in NTB. The results of the study show that the support and commitment of the NTB local government towards halal tourism that was built is based on Ahklak, Adab, and eastern culture. The main scheme is Muslim world tourists. This Akhlak, Adab, and east culture are very important to give a different color and show the local identity of an area. The halal concept was found through the convergence of cultural values and customs of the three tribes in NTB, namely the Sasak, Samawa, and Mbojo (Sasambo) tribes. It is contained and agreed upon in the norms and culture of the community, actualized at specific convergence points. The convergence of Islamic prophetic values with the historical, social benefits of the Sasak, Samawa and Mbojo tribes is seen in terms of halal food patterns, civilized patterns of association, clothing, and other economic trends. Like the Sasambo tribal philosophy “AdatBersendikanSyara’, Syara’ is based on the book of Allah’, which increasingly gives its Islamic identity. These paradigms and philosophies are the principal capital for the creation of regional halal regulations, accommodating local entities that are inherited and civilizedthrough local friendly entities.